Introduction to the special issue - Zach Simpson; Peter Looker (University of Johannesburg, 2018)
Dr Zach Simpson and Prof Peter Looker, the editors of this second, special issue of SOTL in the South, contextualise the papers in the issue in relationship to one another. These articles were select for double-blind peer-review and publication after being presented at the SOTL in the South conference in July 2017 in Johannesburg, South Africa. How to cite this editorial: SIMPSON, Zach; LOOKER, Peter. Editorial: introduction to the special issue. Scholarship of Teaching and Learning in the South. v. 2, n. 1, p. 1-3, Apr. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=52 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/